Comparative characterization of water quality based on physicochemical parameters from various water sources - Yaumil Khairin Septiani; Winny Liliawati; Danny Firmansyah; Ilham Ramdhani; Nur Fadhillah (Journal of Earth Kingdom, 2026)
Background: Water quality varies substantially across source types, yet field-based comparative assessments spanning natural, household-consumable, and potentially contaminated water within a single urban highland setting remain scarce in Indonesia. This study characterized and compared the physicochemical quality of 14 water samples across three source categories in Bandung, West Java, and evaluated their alignment with regulatory standards and product-labeled claims. Methods: Samples were collected through grab sampling and measured in situ using a portable multiparameter pH meter for pH, electrical conductivity (EC), total dissolved solids (TDS), salinity, and temperature. Descriptive statistics and Pearson correlation analysis were performed using IBM SPSS Statistics. Findings: Considerable variation was observed across source categories: mean pH 6.69 ± 0.77, EC 183.24 ± 141.00 μS/cm, TDS 134.86 ± 95.93 ppm, salinity 128.13 ± 90.55 ppm, and temperature 23.24 ± 1.17°C. Six of 14 samples recorded pH below the minimum threshold of 6.5, including tap water (5.20), unboiled gallon water (5.80), two packaged mineral water brands, and both domestic wastewater samples. A very strong positive correlation was found between EC and TDS (r = 0.984, p < 0.001), confirming EC as a reliable field proxy for TDS estimation. Conclusion: Two packaged mineral water products marketed with alkaline pH claims showed discrepancies of more than one pH unit between measured and labeled values. These findings confirm that water source category is a primary determinant of physicochemical quality, underscoring the need for strengthened monitoring of distributed water supply systems and post-market verification of pH claims in Indonesia. Novelty/Originality of this article: The novelty lies in the first integrated field-based comparison across three functionally distinct water source categories combined with systematic verification of alkaline pH label claims in the Indonesian context.